Atmospheric Corrosion Behavior of Carbon Steel and Galvanized Steel after Exposure in Eretan and Ciwaringin, West Java Province, Indonesia - Gadang Priyotomo; Lutviasari Nuraini; Siska Prifiharni; Ahmad Royani; Sundjono Sundjono; Hadi Gunawan; Meng Zheng (Indonesian Journal of Chemistry, 2020)
The investigation of corrosion for carbon steel and galvanized steel has been conducted in the marine atmosphere of Eretan and Ciwaringin Districts, West Java Province. The exposure time of the field test was up to 200 days, and their corrosion rates are determined according to weight loss method. The objective of the work is to elucidate the corrosion behavior of those alloys which is affected by distances from coastline and environmental condition. The magnitude of corrosion rate for carbon steel was 20 times as high as that for galvanized steel in both districts The distance from coastline has significantly affected for the magnitude of corrosion rate, where that both alloys in Ciwaringin is lower than that in Eretan. The deposition of chloride ion in Eretan and Ciwaringin Districts were 4.305 mg/m2 day and 1.863 mg/m2 day, respectively, where the higher chloride ion can tend to increase the corrosion rates. Relative humidity (RH) which is over 60% has essential role for corrosion process as well as rainfall. The uniform corrosion attack was observed both alloys after exposure. The corrosion product phases of galvanized steel exhibits as zincite, hydrozincite and simonkolleite in Eretan as the typical coastline atmosphere phases but not in Ciwaringin. The formation of rust product for both metals lead the decrease of further corrosion attack due to the barrier between metal and environment. The usage of galvanized steel is remarkable to minimize corrosion attack compared to that of carbon steel in tropical coastline.